The reporting of progression criteria in protocols of pilot trials designed to assess the feasibility of main trials is insufficient: a meta-epidemiological study - Lawrence Mbuagbaw; Sarah Daisy Kosa; Daeria O. Lawson; Rosa Stalteri; Oluwatobi R. Olaiya; Ahlam Alotaibi; Lehana Thabane (Pilot and Feasibility Studies, 2019)
Abstract Introduction Pilot and feasibility trials are conducted to determine feasibility or to collect information that would inform the design of a larger definitive trial. Clear progression criteria are required to determine if a definitive or main trial is feasible and how it should be designed. We sought to determine how often progression criteria are reported and the associated factors. Methods We conducted a methodological review of protocols for pilot randomised trials published in three journals that publish research protocols (BMJ Open, Trials, Pilot and Feasibility Studies), using a PubMed search (2013–2017). We extracted bibliometric information including the country in which the study was conducted, source of funding, type of intervention, use of a primary feasibility outcome, sample size reporting, and justification. We used generalised linear models to determine the factors associated with reporting progression criteria. Results Our search retrieved 276 articles, of which 49 were not eligible. We included 227 articles. Overall, 45/227 (19.8%; 95% confidence interval [CI] 14.8–25.6) reported progression criteria. Protocols published in more recent years were significantly associated with higher odds of reporting progression criteria (adjusted odds ratio [aOR] 1.40; 95% CI 1.03–1.92; p = 0.034). Pilot trials from Europe (aOR 0.19; 95% CI 0.08–0.48; p < 0.001) and the rest of the world (aOR 0.05; 95% CI 0.01–0.18; p < 0.003) compared to North America were significantly associated with lower odds of reporting progression criteria. Journal, source of funding, sample size, intervention type, and having a primary outcome related to feasibility were not significantly associated with reporting progression criteria. Conclusion Progression criteria are not often explicitly stated in protocols of pilot trials leaving room for varied interpretation of findings. The development of formal guidance for progression criteria in protocols of pilot trials is warranted.